Rancang Bangun Aplikasi Penilaian Kinerja Guru Berbasis Website Berdasarkan Pedoman Pelaksanaan Penilaian Kinerja Guru Pada SMK Rajasa Surabaya - Yusro, Mochamad Ponco; ., Sulistiowati; Sulistiowati, Sulistiowati; Wardhanie, Ayouvi Poerna; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Rajasa Vocational High School (SMK) is one of the private schools in the city of Surabaya. SMK Rajasa is located at Jalan Genteng Kali no. 27 Surabaya. The results of the interview with the school found that performance appraisal was important to determine whether the teacher was successful or not in working during a predetermined working period which was useful as an objective consideration in teacher guidance. Performance appraisals are also used for bonuses and teacher salaries at SMK Rajasa Surabaya. At this time, several problems were found, namely teacher performance appraisal takes a long time, namely one month. This makes the process of reporting the performance appraisal to the Principal late. Another problem is the calculation of performance appraisal is still done manually by the assessment team so that sometimes mistakes occur. This led the assessment team to recalculate the performance appraisal. The next problem is that the teacher has not been able to see the results of the performance appraisal in the previous period. Therefore, in this study conducted to design and build teacher performance appraisal applications with a checklist method based on guidelines for implementing teacher performance appraisals. The resulting applications include master management, teacher assessment history, teacher performance appraisal, teacher performance appraisal reports, uploading documents to the system at SMK Rajasa Surabaya. Based on the results of testing with the black box contained in the implementation and evaluation chapter of the system, it was found that all functions were running well.